MANAGEMENT OF POLITENESS STRATEGIES AND RHETORICAL DEVICES IN DONALD TRUMP’S SPEECHES DURING THE CONFLICT WITH IRAN: PRAGMATIC VIEW - Khoirun Nisak; Lisetyo Ariyanti (Ma Chung Press, 2021)
The research aims to figure out the use of politeness strategies and rhetorical devices used by Trump and attempt to reveal the behavior and purpose behind the speeches delivered by Donald Trump during the conflict with Iran taken by the videos in The White House channel on YouTube which are published on January 4th and 9th, 2020. This study employs a descriptive qualitative method by involving the theories by (Brown & Levinson, 1987), (Jowett & O’Donnell, 2012), (G., Preminger, & Brogan, 1994), and Wodak (1987). This study found that Donald Trump mostly uses positive politeness to attend his audience’s attraction to reach his goals and based on the data of the occurance of rhetorical devices, Donald Trump mostly uses Ethos in persuasion which means he frequently shows his good characteristic to reveal people’s trust and followed by using manipulation in each of his in order to manipulate people for achieving his purposes.